2016
DOI: 10.2147/ott.s107319
|View full text |Cite
|
Sign up to set email alerts
|

Pemetrexed plus dendritic cells as third-line therapy for metastatic esophageal squamous cell carcinoma

Abstract: This study was conducted to evaluate the toxicity and efficacy of pemetrexed plus dendritic cells (DCs) when administered as third-line treatment for metastatic esophageal squamous cell carcinoma (ESCC). All patients in the study group had previously failed first-line treatment with 5-fluorouracil and cisplatin-based regimens, as well as second-line treatment with taxane-based regimens. A total of 31 patients were treated with pemetrexed (500 mg/m2) plus DCs on day 1, every 3 weeks. DCs were given for one cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The forest plots, Begg’s funnel plots, and sensitivity analyses are shown in Supplementary Figures 1 – 8 according to the logic sequencing of miRNA names. For the included 96 studies, 52 were excluded because the frequency of them evaluating prognostic value of miRNA was equal to 1 3 , 4 , 16 , 18 23 , 26 , 30 , 31 , 39 46 , 48 , 53 , 54 , 56 , 60 , 61 , 64 74 , 77 86 , 92 96 . In addition, although one article reported OS results about miR-193a-5p, it was excluded because it had non-dichotomous miRNA expression value 105 .…”
Section: Resultsmentioning
confidence: 99%
“…The forest plots, Begg’s funnel plots, and sensitivity analyses are shown in Supplementary Figures 1 – 8 according to the logic sequencing of miRNA names. For the included 96 studies, 52 were excluded because the frequency of them evaluating prognostic value of miRNA was equal to 1 3 , 4 , 16 , 18 23 , 26 , 30 , 31 , 39 46 , 48 , 53 , 54 , 56 , 60 , 61 , 64 74 , 77 86 , 92 96 . In addition, although one article reported OS results about miR-193a-5p, it was excluded because it had non-dichotomous miRNA expression value 105 .…”
Section: Resultsmentioning
confidence: 99%
“…Although the results of intervention studies of EGFR inhibitors/monotherapies/combination chemotherapies have been reported, there is no clear evidence to indicate whether third-line therapy might be effective for prolonging the survival [150,[157][158][159][160][161]. In addition, the safety and efficacy of anti-PD-1 antibody therapy have not yet been reported.…”
Section: Explanatory Notementioning
confidence: 99%
“…Not only do they capture and present tumor antigens, but they also activate and modulate immune responses, impacting the mechanisms of tumor immune surveillance and escape ( 9 ). Previous studies have indicated that a combination therapy of pemetrexed and DCs as a third-line treatment for ESCC can significantly improve prognosis and is well-tolerated ( 10 ). Furthermore, in ESCC patients with regions rich in tertiary lymphoid structures, there is an increased infiltration of CD8+ T cells and DCs, which is associated with stronger anti-tumor immune activity ( 11 ).Specifically, conventional dendritic cells (cDCs) play a key role in cross-presenting tumor antigens and activating cytotoxic T cells; tolerogenic dendritic cells (tDCs) can modulate immune responses by inducing immune tolerance or generating regulatory T cells, thereby preventing overactive immune reactions ( 12 ); plasmacytoid dendritic cells (pDCs), primarily known for their role in antiviral responses, have an unclear role in the TME, possibly involving the modulation of the immune status of the TME ( 13 ).…”
Section: Introductionmentioning
confidence: 99%